Gestational diabetes detection thresholds and infant growth, nutrition, and neurodevelopment at 12-18 months: a prospective cohort study within a randomized trial - Amitrano F; Manerkar K; Alsweiler JM; Conlon CA; Crowther CA; Edlin R; Harding JE; McCowan LME; Meyer MP; Rowan JA; Rush EC; McKinlay CJD (Springer Nature Limited, 2025)
Objective To assess the impact of gestational diabetes(GDM) detection thresholds on infant growth, nutrition, and neurodevelopment at 12-18 months. Design Prospective cohort study within the GEMS trial(ACTRN12615000290594), which randomized pregnant women to detection of GDM using lower or higher glycemic criteria. The main outcomes were overweight/rapid weight gain; food approach appetitive score; energy intake; cognitive z-score. Result Compared to control infants, those exposed to GDM detected and treated by higher criteria or by lower but not higher criteria that was untreated, were less likely to have increased overweight/rapid weight gain, possibly with lower energy intake. There were no important differences in appetite and cognition. Infants exposed to GDM by lower but not higher criteria that was treated were similar to controls. Conclusion Exposure to treated GDM or untreated GDM detected by lower but not higher criteria, was not associated with increased infant risk factors for obesity or adverse cognitive outcomes.